ESL LEARNERS’ PERCEPTION ON THE USE OF THE GRAPHIC ORGANIZERS (GOs) AS CLASS PRESENTATION STRATEGIES - Dedi Aprianto; Wahyu Kamil Syarifaturrahman (Universitas Muhammadiyah Makassar, 2020)
The study scientifically, empirically, and objectively conducted aims at knowing the ESL learners’ perceptions towards the practices of graphic organizers conveniently used as presentation media or strategies in high class activities (a class-presentation task). In order to achieve the aim of the study, the researcher used a quantitative research technique along with its instrument, a questionnaire. The data was collected through applying a questionnaire, and then analyzed in a descriptive statistic method. The results suggest that the perceptions of low English speakers in using graphic organizers as presentation strategies was moderate (M=3.7). Meanwhile, ESL learners owning a good English proficiency perceived the use of graphic organizers as presentation strategies positively (M=4.5). All in all, the use of Graphic Organizers (GOs) as ESL learners’ presentation media or strategies was perceived favorably.